Environmental Management of Production Processes in Heating Systems when Receiving Magnetic Water in Reagent-Free Method with the Aim of Environmentalization - Kulikov, Petro; Bondar, Olena; Zhuravska, Nataliia (International Journal of Engineering and Technology, 2018)
It has been proved that the environmental management of industrial systems of a heat supply, under the terms of the application of the method of preparation of reagent-free industrial water depends on ensuring the implementation of its basic principles. It is shown that the electromagnetic interaction of multi factorial criterial components of the process of magnetization of water is performed through the mechanism of feedback in the heating system. And the mechanism of feedback in the heating system is characterized by the properties of loop negative feedback and therefore is auto regulation of the process of magnetization of water takes place. Quantitative indicators of integral system of control over the process of magnetization of water in heating systems were defined. Both the graduation orderliness of mass exchange process and its additive function must be within â‰¤ 1.Â Â